Analisis Penamaan Jalan dan Nilai Historis Kebangsaan di Kota Madiun - Febri Ersa Millenia Puti; Agnes Adhani; Wenny Wijayanti (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
This research is motivated by the existence of street names in Madiun City with the characteristics of each region. This study aims to find the form of naming and describe the meaning of roads in Madiun City. The method used in this research is qualitative, semantic study. Sources of data in this study are street names (places), street naming documents (maps), and historians. The data in this study are in the form of words or phrases of street names in the city of Madiun. Data collection techniques are in the form of documentation in the form of writing and pictures. The data analysis technique in this study consisted of three stages, namely (1) analyzing the naming pattern based on the number of words, the number of syllables, markers, and word classes, (2) analyzing the meaning of street names and associating names with references, and (3) analyzing the existence of whether or not the contribution of historical and national values ​​to street names. This research resulted in finding street names in Madiun City using 2 words, 4 syllables, word classes in the form of nouns, and the most common markers were the names of heroes. Found 14 meanings of street names in Madiun City. The naming of roads receives a contribution of historical value in the form of a change of name and the existence of a marker object, while it receives a contribution of national value through street names in the form of names of heroes and organizations as a commemoration of services and the embodiment of love for Indonesia.